Load and service adaptive algorithm (LSAA) for tight coupling based integration architecture - Aziz, A. (IEEE Computer Society, 2014)
In order to fulfill the anywhere at any time data services demand, integration of existing wireless networks has attained the tremendous attention in last decades. Because of the complimentary characteristics and widest deployment of the Universal Mobile Telecommunication System (UMTS) and Wireless LAN (WLAN) compared to any other wireless access networks, the Next Generation Network considers the integration of these two technologies as the most attractive option for anywhere at any time data services. The UMTS network provides global coverage with low data rate services. On contrary, the WLAN offers high data rate in a limited geographical area. The integration of these two promising networks can deliver better performance and at the same time avoiding the weakness of any individual access network. This research work introduces the Load and Service Adaptive Algorithm (LSAA) for the integrated UMTS/WLAN. In the proposed LSAA algorithm, during the new session establishment, the Mobile Station (MS) collects the available network radio resources information through the Radio Network Controller (RNC). The collected information is further utilized to estimate the available access network for required data session. The MS starts the session establishment procedure to the access network selected by the LSAA. The LSAA algorithm exhibits notable enhancement compare to the without LSAA algorithm, in terms of connection blocking probability and system resource utilization. Â© 2014 IEEE.